Method for preparing copper-tin alloy through injection molding

Through low melting point Sn coating and liquid phase sintering technology, combined with chemical coating and injection molding processes, the problem of insufficient injection molding of traditional copper alloys is solved, and the preparation of copper-tin alloys with high density and performance is achieved.

CN119194141APending Publication Date: 2024-12-27XIAN SIRUI NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411179920.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional copper alloy injection molding and sintering have low density, making it difficult to meet the needs of high-strength, high-thermal conductivity and heat dissipation materials.

Method used

Cu is coated with Sn at low melting point and sintered by liquid phase method. Combined with chemical coating, feeding preparation, pelletizing, injection molding and thermal degreasing sintering processes, a dense copper-tin alloy is formed.

Benefits of technology

It improves the density and performance of copper-tin alloy, reduces pores and defects during sintering, enhances the wear resistance and lubricity of the material, extends the service life, and improves the overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194141A_ABST
    Figure CN119194141A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal alloy preparation, in particular to a method for preparing a copper-tin alloy through injection molding. The method comprises the following steps of S1, chemical coating, S2, feed preparation, S3, banburying granulation, S4, injection molding and S5, thermal degreasing and sintering. According to the tin-plated copper powder prepared through chemical plating and calcination, the surface of the copper powder can be evenly coated with a tin layer, pores and defects in the sintering process can be reduced through the even plating layer, and therefore the density of a sintered body is improved, the uniformity and compactness of the tin-plated layer can be further improved through calcination treatment after chemical tin plating, and the service life of the tin-plated copper powder is prolonged. In addition, as the melting point of Sn is low, densification sintering can be carried out by adopting a liquid phase sintering method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-tin alloy preparation, and in particular to a method for preparing the copper-tin alloy by injection molding. Background Art

[0002] There is a small amount of tin in the chemical composition of CuSn0.15 alloy. This combination of properties allows the alloy to be widely used in various applications, including automobiles and electrical connectors. With the rapid development of electronic communication technology, the demand for high-strength and high-thermal conductivity heat dissipation materials continues to increase. Adding a small amount of Sn element to Cu can improve the strength and heat resistance of the material while ensuring the electrical and thermal conductivity of Cu. CuSn (0%-2%) is a high-strength and high-conductivity copper alloy with high electrical and thermal conductivity. By adding a small amount of tin, the strength, heat resistance, stress relaxation resistance and good bending formability of pure copper are improved, and it is widely used;

[0003] Traditional copper-tin alloys are mainly used for melting and casting to produce plate and strip materials. They are used in automobiles and electrical connectors. Currently, they are mainly produced by mechanical processing. Since the density of traditional copper alloy injection molding sintering is not high, in order to solve the above problems, the present invention decides to use low-melting-point Sn to coat Cu, injection mold, and use liquid phase method for sintering, thereby solving the above problems. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing a copper-tin alloy by injection molding.

[0005] The technical solution of the present invention is: a method for preparing a copper-tin alloy by injection molding, comprising the following steps:

[0006] S1. Chemical coating

[0007] S1-1, adding atomized copper powder to an acid solution with a concentration of 10-100 ml / L according to a mass ratio of 1.5 kg: 1 L, stirring for 25-35 min for surface activation treatment, and then introducing it into a centrifuge for centrifugal treatment, removing the supernatant to obtain a slurry; the average particle size of the atomized copper powder is 10-20 μm; the centrifuge parameters are: centrifugal speed is 4800-5200 r / min, and the centrifugal time is 10 min; the acid solution is hydrofluoric acid solution, hydrochloric acid solution or nitric acid solution;

[0008] S1-2, adding the slurry, 10-20 g / L tin salt solution, 25-30 g / L reducing agent solution, and 10-20 g / L complexing agent solution into a mixing tank in a mass ratio of 1:1:2:2, adjusting the temperature of the mixing tank to 40-70°C, then adding 150 g / L alkali solution to adjust the pH to 11-12, stirring for 2 hours, and then standing and settling for 1-3 hours, removing the supernatant to obtain a precipitated slurry;

[0009] S1-3, calcining the precipitated slurry at 200° C. for 2 h under vacuum atmosphere to obtain a calcined material, crushing the calcined material to 40-50 μm with a jaw crusher, and then crushing the coarse crushed material to within 10-20 μm with a jet mill, and then hot alkali washing with 60° C. 150 g / L alkali solution for 15-20 min, filtering and continuing to wash with industrial pure water for 2-4 times, and finally transferring to a vibration dryer, intermittent vibration drying under vacuum atmosphere conditions, to obtain tin-coated copper powder with a particle size of 20-40 μm;

[0010] S2. Feed preparation

[0011] The feed material includes, by weight percentage, 10% paraffin as a main binder, 3-7% polypropylene / polyethylene as a skeleton binder, 3-5% EVA as a plasticizer, 0.5-1.5% stearic acid as a surfactant, 0.5-1% antioxidant 245, and the balance is polyoxymethylene;

[0012] S3, internal mixing and granulation

[0013] The tin-coated copper powder and the feed are added to an internal mixer in sequence according to the feed accounting for 35-45% of the total volume and 7-11% of the total mass, respectively; the internal mixer is preheated to 170-180° C., and the internal mixer is kneaded at a speed of 30-50 r / min for 1.5-2.5 hours until the internally kneaded material becomes a mass; the internally kneaded material is put into a granulator, and granulated for 1-3 hours at a temperature of 165-175° C., a knife frequency of 440-460 Hz, and an extrusion screw frequency of 35-45 Hz in forward rotation to obtain composite particles;

[0014] S4, injection molding

[0015] At 170-200° C., the composite particles are injected into a mold at a temperature of 110-130° C., and after the injection is completed, the pressure is maintained at 80-120 bar for 1-3 seconds to obtain an injection molded green body;

[0016] S5. Thermal debinding and sintering

[0017] The injection molded green body is placed in a sintering furnace, and then oxalic acid is passed into the furnace at a rate of 2 to 5 g / min for 6 to 10 hours. The temperature in the furnace is maintained at 110 to 130°C during the acid feeding process. Then, the green body is degreased under negative pressure and kept at 800°C for 30 minutes. Finally, it is sintered under slightly negative pressure to obtain a copper-tin alloy.

[0018] Further, in step S1-2, the tin salt solution is any one of tin hydroxide, sodium stannate or potassium stannate; the reducing agent is any one of sodium borohydride, glyoxylic acid, ascorbic acid, dimethoxyethoxyaluminum hydride, and hypophosphite; the complexing agent is any one of ethanolamine, tetrahydroxyhexamethylenediamine, disodium ethylenediaminetetraacetate, potassium sodium tartrate, ammonia water, and EDTA;

[0019] Description: Tin hydroxide, sodium stannate and potassium stannate, as tin sources, can improve the solubility and stability of tin in the solution, thereby affecting the distribution and content of tin in the alloy. Appropriate tin salt concentration and type can also help to form evenly distributed tin particles during the reduction process, which helps to improve the density of the alloy. Strong reducing agents such as sodium borohydride can quickly and effectively reduce tin ions. Complexing agents such as ethanolamine and disodium ethylenediaminetetraacetic acid can stabilize tin ions and prevent them from premature precipitation, thereby forming finer tin particles during the reduction process, thereby improving the density of the alloy.

[0020] Further, in step S1-2 and step S1-3, the alkali solution is potassium hydroxide solution or sodium hydroxide solution;

[0021] Note: Potassium hydroxide and sodium hydroxide are both strong bases that can effectively adjust the pH value of the solution to the alkaline range. By accurately controlling the pH value of the solution, the tin plating reaction can be ensured to proceed smoothly and the performance of the coating can be optimized.

[0022] Furthermore, in step S1-3, the parameters of the intermittent vibration drying are: vibration drying is performed every 2 to 5 minutes, the drying temperature is 125 to 135° C., and the total drying time is 4 to 6 hours;

[0023] Note: Intermittent vibration under the above parameters helps the copper powder particles to maintain a good dispersion state during the drying process, avoids agglomeration and agglomeration between particles, and thus improves the uniformity of the tin plating layer. Vibration drying can promote the diffusion and rearrangement of tin atoms in the tin plating layer, and can also reduce the pores and defects in the plating layer, making the plating layer denser and smoother, which helps to reduce the formation of pores and defects in the subsequent preparation of copper-tin alloy and improve the density of the alloy.

[0024] Furthermore, in step S3, the feeding material is added in the following manner: firstly, paraffin wax and polyoxymethylene are added into an internal mixer, and then tin-coated copper powder is added, and after the temperature in the internal mixer rises to 170-180° C., a skeleton binder, a plasticizer, a surfactant and an antioxidant are added in sequence for internal mixing and granulation;

[0025] Description: Compared with directly adding dry powder and then adding a binder, the method used in this application can reduce the mutual friction between the metal powder and the rotor of the internal mixer. The added paraffin and polyoxymethylene can promote the close bonding of the internal components of the particles, making the particle structure more stable, which helps to reduce the breakage and shedding of the particles during subsequent processing and use, and improve the durability of the copper-tin alloy. The addition of a skeleton binder, a plasticizer, a surfactant and an antioxidant can then be fully mixed at high temperature, which helps to form particles with higher consistency and stability, thereby improving the overall quality of the product.

[0026] Further, in step S5, the debinding method under negative pressure conditions is: evacuate the furnace chamber until the pressure inside the furnace is less than 100Pa, introduce hydrogen to 0.3bar, turn on the ignition device to start heating, and heat to 200°C, 400°C, 500°C, 600°C, and 700°C at a heating rate of 2°C / min, and keep the temperature for 1h each for negative pressure sintering;

[0027] Description: Negative pressure environment can effectively reduce the oxygen content in the furnace, thereby avoiding oxidation of metal materials during the degreasing process. It also helps to extract the gas generated inside the material in time, reduce the formation of defects such as pores, and improve the density and uniformity of the material. Keeping it warm at 200°C can remove volatile organic matter and moisture on the surface of the material. As the temperature rises, the organic matter inside the material gradually decomposes and is removed. The holding time helps these processes to proceed fully. Keeping it warm at 600°C and 700°C can promote the sintering and densification process of the material.

[0028] Further, in step S5, the method of slightly negative pressure sintering is: increase the air intake until the pressure in the furnace is 1-10 Pa less than the atmospheric pressure, and adjust the heating rate to 3°C / min, then heat to 1070°C and keep warm for 5 hours, stop the hydrogen introduction and re-introduce nitrogen at a gas flow rate of 5-10L / h, so that the injection molded green body is cooled to 300°C with the furnace, and then open the rapid nitrogen cooling valve of the sintering furnace at 2-4m 3 / h of gas flow rate to pass nitrogen to cool down to below 60℃ before being taken out of the furnace;

[0029] Note: Slightly negative pressure can cause an outward suction force on the binder in the material. Compared with vacuum sintering, the suction force is small and it is less likely to deform. Compared with slightly positive pressure sintering, it is easier to degrease. The above sintering temperature and holding time can ensure that the powder particles are fully combined, reduce pores and increase density.

[0030] Furthermore, in step S4, the composite particles are subjected to surface strengthening treatment before injection molding, and the surface strengthening treatment method is:

[0031] Ingredients are prepared according to mass percentage: 45-55% fumed silica, 6-8% micro-powder silica gel, 10-15% molybdenum disulfide powder and the balance anhydrous ethanol;

[0032] Molybdenum disulfide powder and 1 / 4 to 1 / 3 of anhydrous ethanol are stirred and mixed at 50 to 60°C to obtain lubricant A, and then micro-powder silica gel and 1 / 3 to 1 / 2 of fumed silica are dissolved in 1 / 4 to 1 / 3 of anhydrous ethanol, and mixed to obtain lubricant B, and the remaining fumed silica and the remaining anhydrous ethanol are mixed to obtain a dispersant.

[0033] The composite particles are subjected to surface treatment, and then lubricant B is added to coat the surface-treated composite particles to obtain a 0.3-0.5 μm adhesion layer and perform a first heat treatment, and then dispersant and lubricant A are alternately coated on the surface of the adhesion layer to obtain a 0.5-0.7 μm composite layer after complete coating and perform a second heat treatment to obtain surface-strengthened composite particles;

[0034] The alternating coating method is as follows: the surface of the attachment layer of the composite particles is divided into 5 rows × 5 columns of rectangular grids, the surface area of ​​one of the rectangular grids is used as the coating unit, and then the dispersant and lubricant A are deposited in each rectangular grid at staggered intervals by microfluidic technology, and each rectangular grid is dried at 30 to 50° C. for 15 to 20 seconds after deposition; the first heat treatment is: purging treatment in a nitrogen atmosphere at 55 to 65° C. for 1 to 3 minutes, and the second heat treatment is: drying in air at 55 to 65° C. for 30 to 60 seconds; the coating components in two adjacent rectangular grids need to be different;

[0035] Description: Micro-powder silica gel has excellent lubricity and wear resistance, which can reduce the friction and wear of copper-tin composite particles during injection molding and improve molding efficiency and quality. Nano-particles of fumed silica have good dispersibility and adhesion, and can form a uniform adhesion layer on the surface of composite particles, providing a better adhesion basis for subsequent coatings. Molybdenum disulfide is an efficient solid lubricant, especially suitable for lubrication under high temperature and high pressure. It can further enhance the lubricity of the surface of copper-tin particles and help maintain the integrity and fluidity of particles during high-temperature injection molding, making it easier to flow in the mold. Fumed silica and anhydrous ethanol can be better dispersed on the surface of composite particles after mixing to form a uniform dispersed coating. The alternating coating method can ensure the uniformity of the coating. and thickness control, while avoiding the interaction between coatings that affects performance. Drying after coating each rectangular grid helps remove the solvent in the coating, making the coating tighter and more stable, and the adhesion layer outside the rectangular grid also has the effect of reducing the dispersion of copper-tin composite particles during injection molding. The nitrogen atmosphere in the first heat treatment can protect the coating from oxidation, and the purge treatment helps remove residual solvents and gases in the coating, improving the density and stability of the coating. The second heat treatment can further consolidate the structure of the coating and promote the bonding between the coating and the composite particles, thereby improving the durability of the coating. On the one hand, anhydrous ethanol can reduce the temperature and prevent powder oxidation. On the other hand, anhydrous ethanol is a dispersant that can reduce the surface energy of the powder surface and prevent powder agglomeration.

[0036] Furthermore, the surface treatment method is: completely immersing the composite particles in an acetone solution, roughly washing them for 15 to 20 minutes at an ultrasonic frequency of 45 to 55 kHz and a temperature of 30 to 40° C., taking them out and drying them in an oven at 55 to 65° C. for 15 to 20 seconds, adjusting the ultrasonic frequency to 75 to 85 kHz and the temperature to 45 to 55° C. to continue fine washing for 10 to 20 minutes, taking them out and drying them in an oven at 85 to 95° C. for 15 to 20 seconds to obtain the surface-treated composite particles;

[0037] Description: The rough washing and fine washing processes can effectively remove impurities such as oil, oxides, dust, etc. on the surface of the copper-tin composite particles. The surface cleanliness of the copper-tin composite particles can be significantly improved through the cleaning of the acetone solution and the oscillation of the ultrasonic wave. The clean surface is conducive to the uniform coating and firm adhesion of the subsequent coating. At the same time, the oscillation of the ultrasonic wave can also improve the roughness of the particle surface to a certain extent, making it smoother, thereby reducing the defects and peeling of the coating.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The tin-coated copper powder prepared by chemical plating and calcination in the present invention can be evenly coated with a layer of tin on the surface of the copper powder, and the coating is relatively dense. This uniform coating can reduce the porosity and defects during the sintering process, thereby improving the density of the sintered body. In contrast, when the atomized alloy powder is directly sintered, the alloy powder itself may have problems such as uneven composition or porosity, which may easily lead to insufficient sintering density. In addition, calcination after chemical tin plating can further improve the uniformity and density of the tin plating layer. During the calcination process, the coating will undergo processes such as rearrangement and densification, thereby reducing porosity and defects, making it easier for the tin-plated copper powder to form a dense sintered body in the subsequent sintering process. In addition, chemical plating and calcination can effectively reduce the O, N, C, and S gas impurity content of the material, which can reduce the introduction of external impurities. In addition, since the melting point of Sn is relatively low, liquid phase sintering can be used for densification sintering.

[0040] (2) The injection molding process feed configured by the present invention can enhance the fluidity of the feed and increase the shape retention of the injection blank during the degreasing process by using polyoxymethylene and paraffin as the main mixed binder. Stearic acid, as a surfactant, can reduce the surface tension during the alloy preparation process, making it easier to mix and disperse the components, thereby improving the density of the alloy. The antioxidant can also maintain the stability and density of the alloy by preventing the occurrence of oxidation reactions. EVA (ethylene-vinyl acetate copolymer) as a plasticizer can improve the flexibility and processing properties of the alloy, and reduce the internal stress and defects of the alloy during the preparation process by increasing the flexibility of the alloy, thereby improving the density of the alloy.

[0041] (3) The present invention can significantly improve the wear resistance and lubricity of the composite particles, extend their service life, and improve their flow in the mold, thereby improving the density of the copper-tin alloy. Through the steps of surface treatment, coating loading and heat treatment, it can ensure that the coating is firmly attached to the surface of the composite particles, thereby forming a good bonding interface in the alloy and improving the overall performance of the alloy. The alternating interval coating method proposed in the present application can ensure that the coating thickness and uniformity in each rectangular grid are controlled, avoiding the uneven coating thickness or accumulation phenomenon that may occur in the traditional coating method, thereby improving the surface quality and consistency of the copper-tin particles. The staggered coating of lubricant A and dispersant can form a composite coating with excellent lubricity, wear resistance and corrosion resistance on the particle surface, thereby improving the overall performance of the copper-tin particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a comparison diagram of the density of the copper-tin alloy obtained in Examples 1 to 7 of the present invention and Comparative Examples 1 to 2;

[0043] Figure 2It is a comparison diagram of the density of the copper-tin alloy obtained in Example 1, Examples 8 to 9 and Comparative Example 3 of the present invention;

[0044] Figure 3 It is a comparison diagram of the density of the copper-tin alloy obtained in Example 1, Examples 10 to 28 and Comparative Examples 4 to 5 of the present invention;

[0045] Figure 4 is a comparison chart of the flowability of the composite particles obtained in Example 1, Examples 10 to 28 of the present invention and Comparative Examples 4 to 5;

[0046] Figure 5 It is a comparison chart of the Brinell hardness of copper-tin alloys obtained in Example 1, Examples 10 to 28 of the present invention and Comparative Examples 4 to 5. DETAILED DESCRIPTION

[0047] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0048] Embodiment 1: A method for preparing a copper-tin alloy by injection molding, comprising the following steps:

[0049] S1. Chemical coating

[0050] S1-1. Add atomized copper powder to acid solution at a mass ratio of 1.5kg:1L and stir for 30 minutes for surface activation treatment, then introduce it into a centrifuge for centrifugal treatment, remove the supernatant to obtain a slurry; the average particle size of the atomized copper powder is 10-20μm; the centrifuge parameters are: centrifugal speed of 5000r / min, centrifugal time of 10min; the acid solution uses a hydrofluoric acid solution with a concentration of 55ml / L;

[0051] S1-2, adding the slurry, 15 g / L tin hydroxide solution, 28 g / L sodium borohydride solution, and 15 g / L ammonia solution into a mixing tank in a mass ratio of 1:1:2:2, adjusting the temperature of the mixing tank to 55°C, and then adding a 150 g / L sodium hydroxide solution to adjust the pH to 11.5, stirring for 2 hours, letting it stand for 2 hours, and removing the supernatant to obtain a precipitated slurry;

[0052] S1-3, calcining the precipitated slurry at 200° C. for 2 h under vacuum atmosphere to obtain a calcined material, crushing the calcined material to 40-50 μm with a jaw crusher, and then crushing the coarse crushed material to within 10-20 μm with a jet mill, and then hot alkali washing with a 60° C. 150 g / L sodium hydroxide solution for 18 min, filtering and washing with industrial pure water for 3 times, and finally transferring to a vibration dryer, intermittent vibration drying under vacuum atmosphere, to obtain tin-coated copper powder with a particle size of 20-40 μm;

[0053] Among them, in step S1-3, the parameters of intermittent vibration drying are: vibration drying is performed every 4 minutes, the drying temperature is 130°C, and the total drying time is 5 hours;

[0054] S2. Feed preparation

[0055] The feed material, calculated by mass percentage, includes: 10% paraffin as the main binder, 5% polypropylene as the skeleton binder, 4% plasticizer EVA, 0.5% surfactant stearic acid, 0.5% antioxidant 245, and the balance is polyoxymethylene;

[0056] S3, internal mixing and granulation

[0057] The tin-coated copper powder and the feed are added into the internal mixer in sequence according to the feed accounting for 40% of the total volume and 9% of the total mass, respectively. The internal mixer is preheated to 175° C. and internally kneaded at a speed of 40 r / min for 2 h until the internally kneaded material becomes a mass. The internally kneaded material is put into a granulator and granulated for 2 h at a temperature of 170° C., a knife frequency of 450 Hz, and an extrusion screw frequency of 40 Hz. Composite particles are obtained;

[0058] In step S3, the feeding material is added in the following manner: paraffin wax and polyoxymethylene are first added into the internal mixer, and then the tin-coated copper powder is added, and after the temperature in the internal mixer rises to 175° C., a skeleton binder, a plasticizer, a surfactant and an antioxidant are added in sequence for internal mixing and granulation;

[0059] S4, injection molding

[0060] At 185°C, the composite particles were injected into a mold at 120°C. After the injection was completed, the pressure was maintained at 100 bar for 2 seconds to obtain an injection molded green body.

[0061] S5. Thermal debinding and sintering

[0062] The injection molded green body is placed in a sintering furnace, and then oxalic acid is introduced into the furnace at an acid feeding rate of 4 g / min for 8 hours. During the acid feeding process, the temperature in the furnace is maintained at 120°C, and then degreased under negative pressure conditions, and kept at 800°C for 30 minutes, and finally sintered under slightly negative pressure conditions to obtain a copper-tin alloy.

[0063] In step S5, the debinding method under negative pressure conditions is: evacuate the furnace chamber until the pressure inside the furnace is less than 100Pa, introduce hydrogen to 0.3bar, turn on the ignition device to start heating, and heat to 200℃, 400℃, 500℃, 600℃, and 700℃ at a heating rate of 2℃ / min, and keep the temperature for 1h each to perform negative pressure sintering;

[0064] In step S5, the method of slightly negative pressure sintering is: increase the air intake until the pressure in the furnace is less than 5Pa of the atmospheric pressure, adjust the heating rate to 3°C / min, then heat to 1070°C and keep warm for 5h, stop the hydrogen introduction and introduce nitrogen again at a gas flow rate of 8L / h, so that the injection molded green body is cooled to 300°C with the furnace, then open the rapid nitrogen cooling valve of the sintering furnace, and cool at 3m 3 / h of gas flow rate of nitrogen to cool to below 60 ℃ before taking out of the furnace.

[0065] Example 2: Different from Example 1, in step S1-1, the stirring time of the surface activation treatment is 25 min, the centrifugal speed is 4800 r / min, and the acid solution is a hydrochloric acid solution with a concentration of 55 ml / L.

[0066] Example 3: Different from Example 1, in step S1-1, the stirring time of the surface activation treatment is 35 min, the centrifugal speed is 5200 r / min, and the acid solution is a nitric acid solution with a concentration of 55 ml / L.

[0067] Example 4: Different from Example 1, in step S1-2, the slurry, 10 g / L tin hydroxide solution, 25 g / L sodium borohydride solution, and 10 g / L ammonia solution are added to a mixing tank in a mass ratio of 1:1:2:2, the temperature of the mixing tank is adjusted to 40°C, and then a 150 g / L sodium hydroxide solution is added to adjust the pH to 11. After stirring for 2 hours, the mixture is allowed to stand for 1 hour and the supernatant is removed to obtain a precipitated slurry.

[0068] Example 5: Different from Example 1, in step S1-2, the slurry, 20 g / L tin hydroxide solution, 30 g / L sodium borohydride solution, and 20 g / L ammonia solution are added to a mixing tank in a mass ratio of 1:1:2:2, the temperature of the mixing tank is adjusted to 70°C, and then a 150 g / L sodium hydroxide solution is added to adjust the pH to 12. After stirring for 2 hours, the mixture is allowed to stand and settle for 3 hours, and the supernatant is removed to obtain a precipitated slurry.

[0069] Embodiment 6: Different from Embodiment 1, in step S1-3, the parameters of intermittent vibration drying are: vibration drying is performed every 2 minutes, the drying temperature is 125°C, and the total drying time is 4 hours.

[0070] Embodiment 7: Different from Embodiment 1, in step S1-3, the parameters of intermittent vibration drying are: vibration drying is performed every 5 minutes, the drying temperature is 135°C, and the total drying time is 6 hours.

[0071] Example 8: Different from Example 1, in step S2, the feed, calculated by mass percentage, includes: 10% paraffin as the main binder, 3% polyethylene as the skeleton binder, 3% plasticizer EVA, 3% surfactant stearic acid, 1% antioxidant 245, and the remainder is polyoxymethylene.

[0072] Example 9: Different from Example 1, in step S2, the feed, calculated by mass percentage, includes: 10% paraffin as the main binder, 5% polyethylene as the skeleton binder, 3% plasticizer EVA, 1.5% surfactant stearic acid, 0.5% antioxidant 245, and the remainder is polyoxymethylene.

[0073] Example 10: Different from Example 1, in step S3, tin-coated copper powder and feed are added to the internal mixer in sequence according to the feed accounting for 35% of the total volume and 7% of the total mass, respectively. The internal mixer is preheated to 170°C and mixed at a speed of 30 r / min for 1.5 hours until the mixed material becomes a lump.

[0074] Example 11: Different from Example 1, in step S3, tin-coated copper powder and feed are added to the internal mixer in sequence according to the feed accounting for 45% of the total volume and 11% of the total mass, respectively. The internal mixer is preheated to 180°C and mixed at a speed of 50 r / min for 2.5 hours until the mixed material becomes a lump.

[0075] Example 12: Different from Example 1, in step S3, granulation is performed for 1 hour at a temperature of 165° C., a flying knife frequency of 440 Hz, and an extrusion screw frequency of 35 Hz to obtain composite particles.

[0076] Example 13: Different from Example 1, in step S3, granulation is carried out for 3 hours at a temperature of 175°C, a flying knife frequency of 460 Hz, and an extrusion screw frequency of 45 Hz to obtain composite particles.

[0077] Example 14: Different from Example 1, in step S4, the composite particles are injected into a mold at a temperature of 110°C at 170°C. After the injection is completed, the pressure is maintained at 80 bar for 1 second to obtain an injection molded green body.

[0078] Example 15: Different from Example 1, in step S4, the composite particles are injected into a mold at a temperature of 130°C at 200°C, and after the injection is completed, the pressure is maintained at 120 bar for 3 seconds to obtain an injection molded green body.

[0079] Example 16: Different from Example 1, in step S5, oxalic acid is introduced into the furnace at a rate of 2 g / min for 6 hours, and the temperature in the furnace is maintained at 110°C during the acid introduction process.

[0080] Example 17: Different from Example 1, in step S5, oxalic acid is introduced into the furnace at a rate of 5 g / min for 10 h, and the temperature in the furnace is maintained at 130°C during the acid introduction process.

[0081] Example 18: Different from Example 1, in step S5, the method of slightly negative pressure sintering is as follows: increase the air intake until the pressure in the furnace is less than 1Pa of the atmospheric pressure, and adjust the heating rate to 3°C / min, then heat to 1070°C and keep warm for 5h, stop the hydrogen introduction and introduce nitrogen again at a gas flow rate of 5L / h, so that the injection molded green body is cooled to 300°C with the furnace, then open the rapid nitrogen cooling valve of the sintering furnace, and cool at 2m 3 / h of gas flow rate of nitrogen to cool to below 60 ℃ before taking out of the furnace.

[0082] Example 19: Different from Example 1, in step S5, the method of slightly negative pressure sintering is as follows: increase the air intake until the pressure in the furnace is less than 10Pa of the atmospheric pressure, and adjust the heating rate to 3°C / min, then heat to 1070°C and keep warm for 5h, stop the hydrogen introduction and introduce nitrogen again at a gas flow rate of 10L / h, so that the injection molded green body is cooled to 300°C with the furnace, then open the rapid nitrogen cooling valve of the sintering furnace, and cool at 4m 3 / h of gas flow rate of nitrogen to cool to below 60 ℃ before taking out of the furnace.

[0083] Embodiment 20: Different from Embodiment 1, in step S4, the composite particles are subjected to surface strengthening treatment before injection molding, and the surface strengthening treatment method is:

[0084] Ingredients are prepared according to mass percentage: 50% fumed silica, 7% micro-powder silica gel, 13% molybdenum disulfide powder and the balance anhydrous ethanol;

[0085] Molybdenum disulfide powder and 7 / 24 anhydrous ethanol were stirred and mixed at 55°C to obtain lubricant A. Then, micro-powdered silica gel and 5 / 12 fumed silica were dissolved in 7 / 24 anhydrous ethanol and mixed to obtain lubricant B. The remaining fumed silica and the remaining anhydrous ethanol were mixed to obtain a dispersant.

[0086] The composite particles are surface treated, and then lubricant B is added to coat the surface treated composite particles to obtain a 0.4 μm adhesion layer and perform a first heat treatment. Then, the dispersant and lubricant A are alternately coated on the surface of the adhesion layer. After the coating is complete, a 0.6 μm composite layer is obtained and a second heat treatment is performed to obtain surface strengthened composite particles. The first heat treatment is: purging treatment in a nitrogen atmosphere at 60° C. for 2 minutes, and the second heat treatment is: drying in air at 60° C. for 45 seconds.

[0087] The surface treatment method is as follows: the composite particles are completely immersed in an acetone solution, roughly washed for 18 minutes at an ultrasonic frequency of 50 kHz and a temperature of 35°C, taken out and dried in an oven at 60°C for 18 seconds, the ultrasonic frequency is adjusted to 80 kHz and the temperature is 50°C for further fine washing for 15 minutes, taken out and dried in an oven at 90°C for 18 seconds to obtain the surface-treated composite particles;

[0088] The alternating coating method is as follows: the surface of the attachment layer of the composite particles is divided into 5 rows × 5 columns of rectangular grids, the surface area of ​​one of the rectangular grids is used as the coating unit, and then the dispersant and lubricant A are deposited in each rectangular grid at intervals by microfluidic technology, and each rectangular grid is dried at 40°C for 18 seconds after deposition.

[0089] In this embodiment, the use of microfluidic technology for zoned deposition on the surface of micronized particles refers to Zhao, CX (2013). Multiphase flow microfluidics for the production of single emulsions and beyond. Lab on a Chip, 13 (12), 2183-2198, and the team of Professor Zhang Pengchao of Wuhan University of Technology: A new strategy for preparing advanced polymer films based on microfluidic laminar flow. The above research shows that through microfluidic technology, the microsphere structure can be modified and functional materials can be added during the microsphere preparation process to prepare polymer particles with specific functions. Microfluidic technology can also be used to accurately control the deposition of different coating materials in different areas on the surface of a single micron-sized particle to achieve zoned coating.

[0090] Example 21: Different from Example 20, the ingredients are prepared according to mass percentage: 45% of fumed silica, 6% of micro-powder silica gel, 10% of molybdenum disulfide powder and the remainder of anhydrous ethanol.

[0091] Example 22: Different from Example 20, the ingredients are prepared according to mass percentage: 55% of fumed silica, 8% of micro-powder silica gel, 15% of molybdenum disulfide powder and the remainder of anhydrous ethanol.

[0092] Example 23: Different from Example 20, molybdenum disulfide powder and 1 / 4 anhydrous ethanol were stirred and mixed at 50°C to obtain lubricant A, and then micro-powder silica gel and 1 / 3 of fumed silica were dissolved in 1 / 4 anhydrous ethanol and mixed to obtain lubricant B, and the remaining fumed silica and the remaining anhydrous ethanol were mixed to obtain a dispersant.

[0093] The composite particles are surface treated, and then lubricant B is added to coat the surface treated composite particles to obtain a 0.3 μm adhesion layer and perform the first heat treatment. Dispersant and lubricant A are then alternately coated on the surface of the adhesion layer to obtain a 0.5 μm composite layer after complete coating and perform the second heat treatment to obtain surface strengthened composite particles. The first heat treatment is: purging treatment in a nitrogen atmosphere at 55°C for 1 minute, and the second heat treatment is: drying in air at 55°C for 30 seconds.

[0094] Example 24: Different from Example 20, molybdenum disulfide powder and 1 / 3 of anhydrous ethanol were stirred and mixed at 60°C to obtain lubricant A, and then micro-powder silica gel and 1 / 2 of fumed silica were dissolved in 1 / 3 of anhydrous ethanol and mixed to obtain lubricant B, and the remaining fumed silica and the remaining anhydrous ethanol were mixed to obtain a dispersant.

[0095] The composite particles are surface treated, and then lubricant B is added to coat the surface treated composite particles to obtain a 0.5 μm adhesion layer and perform the first heat treatment. Dispersant and lubricant A are then alternately coated on the adhesion layer surface to obtain a 0.7 μm composite layer after complete coating and perform the second heat treatment to obtain surface strengthened composite particles. The first heat treatment is: purging treatment for 3 minutes in a nitrogen atmosphere at 65°C, and the second heat treatment is: drying in air at 65°C for 60 seconds.

[0096] Example 25: Different from Example 20, the surface treatment method is as follows: completely immerse the composite particles in acetone solution, roughly wash them for 15 minutes at an ultrasonic frequency of 45 kHz and a temperature of 30°C, remove them and dry them in an oven at 55°C for 15 seconds, adjust the ultrasonic frequency to 75 kHz and the temperature to 45°C to continue fine washing for 10 minutes, remove them and dry them in an oven at 85°C for 15 seconds to obtain the surface-treated composite particles.

[0097] Example 26: Different from Example 20, the surface treatment method is as follows: completely immerse the composite particles in acetone solution, roughly wash them at an ultrasonic frequency of 55 kHz and a temperature of 40°C for 20 minutes, remove them and dry them in an oven at 65°C for 20 seconds, adjust the ultrasonic frequency to 85 kHz and the temperature to 55°C to continue fine washing for 20 minutes, remove them and dry them in an oven at 95°C for 20 seconds to obtain the surface-treated composite particles.

[0098] Example 27: Different from Example 20, the alternating coating method is as follows: the surface of the attachment layer of the composite particles is divided into 5 rows × 5 columns of rectangular grids, and the surface area of ​​one of the rectangular grids is used as the coating unit. The dispersant and lubricant A are then deposited in each rectangular grid at staggered intervals through microfluidic technology. After each rectangular grid is deposited, it is dried at 30°C for 15 seconds.

[0099] Example 28: Different from Example 20, the alternating coating method is as follows: the surface of the attachment layer of the composite particles is divided into 5 rows × 5 columns of rectangular grids, and the surface area of ​​one of the rectangular grids is used as the coating unit. The dispersant and lubricant A are then deposited in each rectangular grid at staggered intervals by microfluidic technology. After each rectangular grid is deposited, it is dried at 50°C for 20 seconds.

[0100] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention;

[0101] First, use a balance to measure the mass of the object and record it as m. Then, add an appropriate amount of water to the measuring cylinder and record the volume of the water as V1. Use a thin wire to tie the object and slowly slide it down the wall of the measuring cylinder until the object is completely immersed in the water. Record the total volume of the water and the object as V2. Finally, use the density formula Calculate the density of tungsten copper alloy;

[0102] Then, the time required for 50 g of the composite particles in different embodiments and control examples to flow through a standard funnel with an aperture of 2.5 mm was tested using the standard funnel method-Hall flow meter;

[0103] The Brinell hardness of the copper-tin alloy in different embodiments and control examples was tested using the Metal Hardness Test GB / T231.1-2002. The results are as follows:

[0104] 1. Investigate the influence of tin-coated copper powder preparation process on the performance of copper-tin alloy.

[0105] Comparative Example 1: Different from Example 1, the atomized copper-tin alloy powder is directly calcined at 200° C. for 2 h to obtain tin-coated copper powder.

[0106] Comparative Example 2: Different from Example 1, the drying method is vibration drying.

[0107] Conclusion: Figure 1It can be seen that the activation treatment parameters of the atomized copper powder in Examples 1 to 7 are too large or too small, the concentrations of the tin-containing salt solution, the reducing agent solution, and the complexing agent solution are too large or too small, and the parameters of the intermittent vibration drying are too large or too small, which will affect the density performance of the copper-tin alloy. Under the parameters of Example 1, the copper-tin alloy with the best performance can be obtained. From the comparison of Examples 1 to 5 and Control Example 1, it can be seen that the direct sintering of the atomized alloy powder in Control Example 1 significantly reduces the density of the copper-tin alloy finally obtained. The preparation method of chemical plating and calcination in the present application makes it easier for the tin-plated copper powder to form a dense sintered body in the subsequent sintering process, thereby having The density of the copper-tin alloy is effectively improved; from the comparison of Example 1, Examples 6-7 and Control Example 2, it can be seen that in Control Example 2, intermittent operation is not performed during the vibration drying process, which will also cause the density of the copper-tin alloy to weaken. This is because intermittent vibration drying can make the composite particles have a more uniform temperature distribution and stress release, which helps to improve the bonding between the copper-tin particles and promote the close bonding of the particles during the injection molding process. In addition, appropriate intermittent vibration drying helps to improve the surface quality of the particles and reduce surface cracks or damage caused by excessive drying or vibration. However, the lack of intermittent operation in Control Example 2 will result in loose bonding of the particles, thereby affecting the density of the alloy.

[0108] 2. Explore the influence of feed composition and ratio on the properties of copper-tin alloy

[0109] Comparative Example 3: Different from Example 1, the feed does not contain antioxidant 245.

[0110] Conclusion: Figure 2It can be seen that from the comparison of Examples 1 and 9, the density of the copper-tin alloy obtained by reducing the plasticizer EVA in Example 9 compared with that in Example 1 and increasing the surfactant stearic acid compared with that in Example 1 is less affected. The main reason is that EVA usually plays a role in reducing the interfacial tension between the two phases and reducing the size of the dispersed phase particles in the alloy, and the reduction in the proportion of EVA may cause the dispersed phase particles to increase in size, which will slightly affect the microstructure and density of the alloy. However, the increased stearic acid will improve the interface bonding between the alloy particles and promote the close bonding of the particles during the injection molding process, thereby improving the density of the alloy. Therefore, the density difference of the copper-tin alloy between Example 1 and Example 9 is small; and from the comparison of Examples 8 and 9, it can be seen that the content of the skeleton binder is reduced, while the surfactant stearic acid and the antioxidant 24 The increase in the content of 5 will cause the density of the copper-tin alloy to decrease. Although stearic acid, as a surfactant, can improve the wettability and dispersibility of the material, improve the mixing uniformity of the alloy components, and help form a denser microstructure, the reduction in the content of the skeleton binder may cause the microstructure of the alloy to become loose, the porosity to increase, and the density of the alloy to be more obvious. By comparing Example 1, Examples 8 to 9 and Control Example 3, it can be seen that the density of the copper-tin alloy obtained in Control Example 3 is significantly reduced. This is mainly because the copper-tin particles and the surrounding resin matrix are prone to oxidative degradation in the high temperature and high pressure environment of injection molding. The main function of the antioxidant 245 is to prevent or slow down this oxidation process, thereby protecting the performance of the material from damage, reducing the performance degradation of the material caused by oxidation, and effectively improving the density of the copper-tin alloy.

[0111] 3. Explore the influence of injection molding process on the performance of copper-tin alloy

[0112] Control Example 4: Different from Example 20, the molybdenum disulfide powder in the ingredients is replaced by talcum powder.

[0113] Control Example 5: Different from Example 20, the dispersant is first coated on the surface of the adhesion layer, and then the lubricant A is coated on the surface of the dispersant, without alternating coating.

[0114] Conclusion: Figures 3 to 5From the comparison of Example 1 and Examples 10 to 19, it can be seen that if the process parameters of mixing granulation, injection molding and hot degreasing and sintering are too large or too small, the performance of the copper-tin alloy will be affected, and it can be seen from the figure that under the parameter state of Example 1, the performance of the copper-tin alloy is the best; from the comparison of Example 1 and Examples 20 to 28, it can be seen that the performance of the copper-tin alloy obtained in Examples 20 to 28 is better than that in Example 1, which shows that the surface strengthening treatment of the composite particles further improves the flowability of the composite particles, thereby enhancing the preparation effect of the composite particles in the injection molding process and enhancing the density performance of the copper-tin alloy; from Examples 20 to 22 and Control Example 4, the replacement of molybdenum disulfide powder with talcum powder results in a significant weakening of the performance of the copper-tin alloy obtained, and the Brinell hardness also appears The main reason is that when molybdenum disulfide is added to fumed silica or micro-powder silica gel, it can not only serve as a lubricating component, but also as a reinforcing phase to improve the mechanical properties of the composite material, such as Brinell hardness. By comparing Example 20, Example 23-Example 24 and Example 27-Example 28 with Control Example 5, it can be seen that the direct coating in Control Example 5 has limited effect on improving the performance of the copper-tin particles, while the alternating interval coating method can ensure that the coating thickness and uniformity in each rectangular grid are controlled, avoiding the coating accumulation phenomenon, thereby improving the surface quality and consistency of the copper-tin particles. The staggered coating of lubricant A and dispersant can form a composite coating with excellent lubricity, wear resistance and hardness on the particle surface, thereby improving the overall performance of the copper-tin particles. In summary, Example 20 is the best solution.

Claims

1. A method for preparing a copper-tin alloy by injection molding, characterized in that: The following steps are involved: S1. Chemical coating S1-1, adding atomized copper powder to an acid solution with a concentration of 10-100 ml / L according to a mass ratio of 1.5 kg: 1 L, stirring for 25-35 min for surface activation treatment, and then introducing it into a centrifuge for centrifugal treatment, removing the supernatant to obtain a slurry; the average particle size of the atomized copper powder is 10-20 μm; the centrifuge parameters are: centrifugal speed is 4800-5200 r / min, and the centrifugal time is 10 min; the acid solution is hydrofluoric acid solution, hydrochloric acid solution or nitric acid solution; S1-2, adding the slurry, 10-20 g / L tin salt solution, 25-30 g / L reducing agent solution, and 10-20 g / L complexing agent solution into a mixing tank in a mass ratio of 1:1:2:2, adjusting the temperature of the mixing tank to 40-70°C, then adding 150 g / L alkali solution to adjust the pH to 11-12, stirring for 2 hours, and then standing and settling for 1-3 hours, removing the supernatant to obtain a precipitated slurry; S1-3, calcining the precipitated slurry at 200° C. for 2 h under vacuum atmosphere to obtain a calcined material, crushing the calcined material to 40-50 μm with a jaw crusher, and then crushing the coarse crushed material to within 10-20 μm with a jet mill, and then hot alkali washing with 60° C. 150 g / L alkali solution for 15-20 min, filtering and continuing to wash with industrial pure water for 2-4 times, and finally transferring to a vibration dryer, intermittent vibration drying under vacuum atmosphere conditions, to obtain tin-coated copper powder with a particle size of 20-40 μm; S2. Feed preparation The feed material includes, by weight percentage, 10% paraffin as a main binder, 3-7% polypropylene / polyethylene as a skeleton binder, 3-5% EVA as a plasticizer, 0.5-1.5% stearic acid as a surfactant, 0.5-1% antioxidant 245, and the balance is polyoxymethylene; S3, internal mixing and granulation The tin-coated copper powder and the feed are added to an internal mixer in sequence according to the feed accounting for 35-45% of the total volume and 7-11% of the total mass, respectively; the internal mixer is preheated to 170-180° C., and the internal mixer is kneaded at a speed of 30-50 r / min for 1.5-2.5 hours until the internally kneaded material becomes a mass; the internally kneaded material is put into a granulator, and granulated for 1-3 hours at a temperature of 165-175° C., a knife frequency of 440-460 Hz, and an extrusion screw frequency of 35-45 Hz in forward rotation to obtain composite particles; S4, injection molding At 170-200° C., the composite particles are injected into a mold at a temperature of 110-130° C., and after the injection is completed, the pressure is maintained at 80-120 bar for 1-3 seconds to obtain an injection molded green body; S5. Thermal debinding and sintering The injection molded green body is placed in a sintering furnace, and then oxalic acid is passed into the furnace at a rate of 2 to 5 g / min for 6 to 10 hours. The temperature in the furnace is maintained at 110 to 130°C during the acid feeding process. Then, the green body is degreased under negative pressure and kept at 800°C for 30 minutes. Finally, it is sintered under slightly negative pressure to obtain a copper-tin alloy.

2. A method for preparing a copper-tin alloy by injection molding as claimed in claim 1, characterized in that: In step S1-2, the tin salt solution is any one of tin hydroxide, sodium stannate or potassium stannate; the reducing agent is any one of sodium borohydride, glyoxylic acid, ascorbic acid, dimethoxyethoxyaluminum hydride, and hypophosphite; and the complexing agent is any one of ethanolamine, tetrahydroxyhexamethylenediamine, disodium ethylenediaminetetraacetate, potassium sodium tartrate, ammonia water, and EDTA.

3. The method for preparing a copper-tin alloy by injection molding according to claim 1, characterized in that: In step S1-2 and step S1-3, the alkali solution is potassium hydroxide solution or sodium hydroxide solution.

4. The method for preparing a copper-tin alloy by injection molding according to claim 1, characterized in that: In step S1-3, the parameters of the intermittent vibration drying are: vibration drying is performed every 2 to 5 minutes, the drying temperature is 125 to 135°C, and the total drying time is 4 to 6 hours.

5. The method for preparing a copper-tin alloy by injection molding according to claim 1, characterized in that: In step S3, the feeding material is added in the following manner: paraffin wax and polyoxymethylene are first added into an internal mixer, and then tin-coated copper powder is added, and after the temperature in the internal mixer rises to 170-180° C., a skeleton binder, a plasticizer, a surfactant and an antioxidant are added in sequence for internal mixing and granulation.

6. The method for preparing a copper-tin alloy by injection molding according to claim 1, characterized in that: In step S5, the method for debinding under negative pressure conditions is: evacuate the furnace chamber until the pressure inside the furnace is less than 100Pa, introduce hydrogen to 0.3bar, turn on the ignition device to start heating, and heat to 200℃, 400℃, 500℃, 600℃, and 700℃ at a heating rate of 2℃ / min, and keep warm for 1h each for negative pressure sintering.

7. The method for preparing a copper-tin alloy by injection molding according to claim 1, characterized in that: In step S5, the method of slightly negative pressure sintering is: increase the air intake until the pressure in the furnace is 1-10 Pa less than the atmospheric pressure, and adjust the heating rate to 3°C / min, then heat to 1070°C and keep warm for 5 hours, stop the hydrogen introduction and introduce nitrogen again at a gas flow rate of 5-10 L / h, so that the injection molded green body is cooled to 300°C with the furnace, and then open the rapid nitrogen cooling valve of the sintering furnace at 2-4 m 3 / h of gas flow rate of nitrogen to cool to below 60 ℃ before taking out of the furnace.

8. The method for preparing a copper-tin alloy by injection molding according to claim 1, characterized in that: In step S4, the composite particles are subjected to surface strengthening treatment before injection molding, and the surface strengthening treatment method is: Ingredients are prepared according to mass percentage: 45-55% fumed silica, 6-8% micro-powder silica gel, 10-15% molybdenum disulfide powder and the balance anhydrous ethanol; Molybdenum disulfide powder and 1 / 4 to 1 / 3 of anhydrous ethanol are stirred and mixed at 50 to 60°C to obtain lubricant A, and then micro-powder silica gel and 1 / 3 to 1 / 2 of fumed silica are dissolved in 1 / 4 to 1 / 3 of anhydrous ethanol, and mixed to obtain lubricant B, and the remaining fumed silica and the remaining anhydrous ethanol are mixed to obtain a dispersant. The composite particles are subjected to surface treatment, and then lubricant B is added to coat the surface-treated composite particles to obtain a 0.3-0.5 μm adhesion layer and perform a first heat treatment, and then dispersant and lubricant A are alternately coated on the surface of the adhesion layer to obtain a 0.5-0.7 μm composite layer after complete coating and perform a second heat treatment to obtain surface-strengthened composite particles; Among them, the alternating coating method is: dividing the surface of the attachment layer of the composite particles into 5 rows × 5 columns of rectangular grids, taking the surface area of ​​one of the rectangular grids as the coating unit, and then depositing the dispersant and lubricant A in each rectangular grid at staggered intervals by microfluidic technology, and drying each rectangular grid at 30-50°C for 15-20s after deposition; the first heat treatment is: purging treatment in a nitrogen atmosphere at 55-65°C for 1-3min, and the second heat treatment is: drying in air at 55-65°C for 30-60s.

9. A method for preparing a copper-tin alloy by injection molding as claimed in claim 8, characterized in that: The surface treatment method is as follows: completely immersing the composite particles in an acetone solution, roughly washing them for 15 to 20 minutes at an ultrasonic frequency of 45 to 55 kHz and a temperature of 30 to 40° C., taking them out and drying them in an oven at 55 to 65° C. for 15 to 20 seconds, adjusting the ultrasonic frequency to 75 to 85 kHz and the temperature to 45 to 55° C. to continue fine washing for 10 to 20 minutes, taking them out and drying them in an oven at 85 to 95° C. for 15 to 20 seconds to obtain the surface-treated composite particles.

Citation Information

Cited By

  • Hydrogen sintering furnace convenient to clean

    CN121916658A

  • Hydrogen sintering furnace convenient to clean

    CN121916658B